COMPARATIVE STUDIES OF LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF CICHLIDAE SPECIES (Oreochromis nilotucus (Linneus, 1758) AND Sarotherodon melanotheron (Ruppell, 1852) OF GUBI RESERVOIR, BAUCHI STATE, NIGERIA - Alkasim, Adurrashid; Bukar, Modu A.; Dauda, Aliyu M. (FUDMA Journal of Sciences, 2025)
The objective of the research was to assess the length-weight and condition factor of Cichlidae: Oreochromis niloticus and Sarotherodon melanotheron. The research carried out for eighteen months February 2024-July 2025. 360 fish sampled were assessed, 180 each specie and 90 each male and female compared. The result of fish length-weight relationship subjected to (W = aLb) results recorded b value for males Oreochromis niloticus 2.1306 and 0.6211 male Sarotherodon melanotheron; 1.7497 female Oreochromis niloticus, 01.1396 female Sarotherodon melanotheron; combined sexes 1.6831 Oreochromis niloticus, 0.8189 Sarotherodon melanotheron. The results indicated negative allometric growth pattern. Linear regression analysis at (P>0.05) with no significant difference for males Oreochromis niloticus 0.8248, Sarotherodon melanotheron 0.3821; females 0.7783 Oreochromis niloticus, 0.5916 Sarotherodon melanotheron; combined sexes 0.6936 Oreochromis niloticus, 0.8561 Sarotherodon melanotheron. Monthly mean condition factor subjected to (K = W×100/ L3) males Oreochromis niloticus ranged 0.026 to 0.098, Sarotherodon melanotheron 0.022 to 0.087; Female Oreochromis niloticus 0.034 to 0.11, Sarotherodon melanotheron 0.012 to 0.215; combined sexes Oreochromis niloticus 0.046 to 0.087, Sarotherodon melanotheron 0.023 to 0.240. The mean condition factors of two species were less than 1, indicating poor condition. The study will serve as reference for future research works.
Keywords: Comparative; Allometric; Isometric; Relationship; Morphometric